Learning Italian as a Second Language in a Sample of Ukrainian Children: A Game-Based Learning Approach - Alessandro Frolli; Francesco Cerciello; Clara Esposito; Mariagrazia Russo; Fabio Bisogni (Pediatric Reports, 2023)
Game-based learning is an educational approach aimed at acquiring knowledge through the use of play. There are various studies that note the effectiveness of playing as an educational tool and the use of digital platforms as a tool that can increase its effectiveness. We wanted to investigate whether a game-based learning approach may determine an improvement in Italian as a foreign language in terms of vocabulary expansion. The sample consists of 48 Ukrainian children between 6 and 7 years old. There were 24 female children and 24 male children in the sample, divided into two groups: the control group (Gr1) learnt Italian through frontal lessons (traditional approach), the experimental group (Gr2) learnt Italian through games and activities (game-based learning). The results have shown that the experimental group had a major increase in Italian vocabulary. However, both groups had an increase in this sense. Game-based learning remains an effective and promising educational approach, but other variables must be taken into account. Furthermore, the scarcity of literature on foreign language learning through game-based learning creates the need for more studies.